Comparison of small versus large intracoronary thrombus burden on angiographic and short-term outcomes in patients undergoing primary PCI - Muhammad Shahzad Fareed; Muhammad Ikram Farid; Badar Ul Ahad Gill; Mubashir Sherwani; Momin Rasheed; Masood Ahmad Khan (Medical Journal of South Punjab, 2025)
Objective: To compare the angiographic and short-term clinical outcomes of small vs. large intracoronary thrombus in patients undergoing Primary PCI. Methodology: A prospective comparative study was conducted at the CPEIC, Multan, from 10-04-2024 to 31-04-2025. Three hundred thirty patients with STEMI were enrolled, and the thrombus burden was analysed. Patients with thrombus grades of 0-2 were labelled as small thrombus burden (STB), and those with ?3 were considered large (LTB). The primary outcome variables were TIMI III flow (procedural success), 30-day mortality and 30-day re-infarction. Qualitative data was compared using the Chi-square test, and quantitative data with an independent t-test. Results: Out of 330 patients, there were 160 (48.5%) with STB and 170 (51.5%) with Large TB. No significant differences were observed in STEMI types (anterior wall: 58.1% vs. 60.0%, p=0.809; inferior wall: 32.5% vs. 29.4%) or culprit vessels (left anterior descending: 61.9% vs. 64.7%, p=0.765; right coronary artery: 32.5% vs. 31.2%). Mortality was higher in the STB group (11.9% vs. 5.9%, p=0.05), while re-infarction rates were comparable (8.8% vs. 7.1%, p=0.569). Procedural success (TIMI III flow) was significantly higher in STB (95.6% vs. 88.8%; p=0.022). Conclusion: Although the angiographic differences for thrombus burden were insignificant, small thrombus burden was associated with relatively more procedural success, 30-day mortality and 30-day reinfarction.